2013
DOI: 10.1158/1541-7786.mcr-13-0214
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 Is Downregulated in Gastric Cancer and Leads to G1-phase Arrest via NF-κB/Cyclin D1 Signaling

Abstract: Sirtuin 1 (SIRT1) is a class III histone/protein deacetylase, and its activation status has been well documented to have physiologic benefits in human health. However, the function of SIRT1 in cancer remains controversial. Here, the expression and role of SIRT1 in gastric cancer is delineated. SIRT1 was present in all normal gastric mucosa specimens; however, it was only present in a portion of the matched gastric cancer tumor specimens. In SIRT1-positive tumors, both mRNA and protein levels were downregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 37 publications
(50 reference statements)
8
72
0
Order By: Relevance
“…So, this inhibitory effect of FBXO31 on colony formation ability was dependent on its F-box domain. The cell cycle arrest is an important anti-proliferation mechanism in cancer [5,18, 19]. Therefore,we used flow cytometry to analyze the cell cycle and determine if the mechanism of the growth suppression of FBXO31 is due to the effect on the cell cycle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…So, this inhibitory effect of FBXO31 on colony formation ability was dependent on its F-box domain. The cell cycle arrest is an important anti-proliferation mechanism in cancer [5,18, 19]. Therefore,we used flow cytometry to analyze the cell cycle and determine if the mechanism of the growth suppression of FBXO31 is due to the effect on the cell cycle.…”
Section: Resultsmentioning
confidence: 99%
“…BGC-823 GC cells transfected with pCMV-myc or pCMV-myc-FBXO31 (5×10 5 viable cells in 0.1 mL PBS) were subcutaneously injected into the two flank region of each mouse. After 1 week, the subcutaneous tumor size was measured every 7 days with a vernier caliper and the tumor volume was calculated by the formula (length)×(width 2 )/2 [5]. The mice were sacrificed after 4 weeks and the dissected tumors were collected and weighed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of Sirt1 is increased in hepatocellular carcinoma [10][11], lung cancer [12], pancreatic cancer [13], however it is reduced in gastric cancer [14], breast cancer [15]. For this reason, it remains ambiguous whether the up-regulated expression of sirt1 indicates a good prognosis or not.…”
mentioning
confidence: 99%
“…Meanwhile, these studies also revealed that sirt1 expression is linked with many clinicopathological characteristics [10][11][12][13][14][15],some studies revealed that sirt1…”
mentioning
confidence: 99%